Understanding Archaeological Heritage Narratives From The Perspective Of Local Community Of Lenggong Valley - Balan, Yugeetha; Md Noor, Shuhaida; Siarap, Kamaliah (2015)
This paper explores the ways in which local community understand and value archeological heritage, focusing on the perspectives of the Lenggong Valley World Heritage site community. The communication and interpretation of archaeological heritage mostly emphasizes the expert’s rather than the community’s perspective. This research investigates the narratives of the Lenggong Valley community as the medium of communicating the sociological aspects of archaeological heritage. This paper presents the preliminary report on the different forms of narratives that were used by the local community when they were approached to explain their understanding of the Lenggong Valley World Heritage Sites. Semi structured interviews were conducted with thirty local community individuals of various age groups, gender and community roles. The respondents are chosen to provide the layperson’s perspectives in understanding archaeological. Interpretive thematic analysis is utilized to understand the responses and to map the narratives. The findings reveal four key forms of narratives that are commonly used by the local community in communicating their interpretation of heritage, namely meta-stories, folktales, myths and legends. The narratives serve to define meanings and values of archaeological heritage to the community and contribute to their sense of community as its help to define relationship with natural environment, making sense of world around them and give insights into local history and beliefs.